(untitled) (Bangladesh Journal of Agricultural Research, 2023)
A study on performance of seven mandarin genotypes along with BARI Komala-1 as check was carried out at the Citrus Research Station, Bangladesh Agricultural Research Institute (BARI), Jaintapur, Sylhet from January 2016 to December 2018. The average highest number of fruits per plant (37.2), and the maximum fruit yield per plant (6.19 kg) and the maximum fruit yield per hectare (6.87 t) were recorded in the genotype CR Jai-017. The largest fruits (189.67 g) were found in the genotype CR Jai-015 (189.67 g) with the maximum fruit size. Edible portion was found the highest in CR Jai-017 (73.52%) followed by CR Jai-018(72.55%). The genotype CR Jai-016 gave the maximum percent total soluble solids (TSS) (13.58%) and the minimum (9.87) in CR Jai-015, whereas, the titratable acidity (TA) value was the lowest in CR Jai-014 (0.73%) followed by CR Jai-017 (0.75). Maturity index (MI)/sugar acid ratio (17.83) was found in CR Jai-016 followed by CR Jai-017 (15.46). Fruits of CR Jai-017 and CR Jai- 018 were dark orange colored. Fruit surface was smooth in BARI Komala-1 and CR Jai-015 whereas other genotypes with pitted skin. The genotype CR Jai-014 has a strong adherence of albedo to pulp, while others were medium to weak. Segment shape of CR Jai-014 and CR Jai-017 were not uniform but the others were uniform. Thickness of segment wall was medium to thick while fruit axis was semi hollow to hollow with light orange to dark orange pulp and pulp firmness was soft to intermediate with medium to high juice content in all the genotypes. Bangladesh J. Agril. Res. 46(3): 245-259, September 2021